2020
DOI: 10.1007/s40200-019-00482-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of remote patient monitoring (RPM) systems for patients with type 2 diabetes: a systematic review and meta-analysis

Abstract: Introduction The objective of this study is to conduct an assessment of Remote Patient Monitoring (RPM) systems compared to usual care for controlling glycosylated hemoglobin in type 2 diabetes. Methods The study was a systematic review with meta-analysis and meta-regression. A systematic search was performed via the most important electronic databases of medical resources, such as PubMed, Scopus and Cochrane library. The main outcome was HbA1C. The heterogeneity sources were examined using Chi-square (Q) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
0
25
0
1
Order By: Relevance
“…Most previous studies on telemedicine for diabetes focused on the effect of telemedicine on the ability to self-manage diabetes [ 12 ], the impact of certain interventions on T2DM self-management [ 13 ] that are not specific to the primary health care setting [ 14 ], and other specific aspects [ 15 ]. Although there have been published reviews of the effectiveness of telemedicine research [ 16 , 17 ] on diabetes, there is a lack of analysis of all the potential outcomes and the impact of telemedicine interventions on patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies on telemedicine for diabetes focused on the effect of telemedicine on the ability to self-manage diabetes [ 12 ], the impact of certain interventions on T2DM self-management [ 13 ] that are not specific to the primary health care setting [ 14 ], and other specific aspects [ 15 ]. Although there have been published reviews of the effectiveness of telemedicine research [ 16 , 17 ] on diabetes, there is a lack of analysis of all the potential outcomes and the impact of telemedicine interventions on patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several meta‐analyses reviewed the effectiveness of technology‐supported self‐management interventions for patients with diabetes (Bonoto et al, 2017; Feigerlova et al, 2020; Hou et al, 2018; Michaud et al, 2020; Salehi et al, 2020). Drawing solid conclusions on the effectiveness of smartphone application–based interventions remains difficult.…”
Section: Introductionmentioning
confidence: 99%
“… 63 A 2020 systematic review and meta-analysis of remote monitoring and telehealth technologies in patients with diabetes reported significant reductions in HbA1c levels. 57 Importantly, a subgroup analysis showed that remote patient monitoring is effective for patients who are residents of cities, especially when using monitoring software (e.g., Dexcom Clarity, Abbott LibreView, Medtronic CareLink) as a component of the intervention.…”
Section: Evidence Supporting Cgm Use In Various Diabetes Populationsmentioning
confidence: 99%